2003
DOI: 10.1194/jlr.m200380-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Lipid compositional analysis of pulmonary surfactant monolayers and monolayer-associated reservoirs

Abstract: Pulmonary surfactant is a lipid:protein complex containing dipalmitoyl-phosphatidylcholine (DPPC) as the major component. Recent studies indicate adsorbed surfactant films consist of a surface monolayer and a monolayerassociated reservoir. It has been hypothesized that the monolayer and its functionally contiguous reservoir may be enriched in DPPC relative to bulk phase surfactant. We investigated the compositional relationship between the monolayer and its reservoir using paper-supported wet bridges to transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 62 publications
5
70
0
Order By: Relevance
“…It is interesting to note that mLPCAT1 also used LPG as an acceptor (Fig. 5A), because pulmonary surfactant contains PG, in addition to DPPC (41). Elucidation of the roles of mLPCAT1 in the production of components of surfactant, and in other biological processes awaits gene-targeting studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that mLPCAT1 also used LPG as an acceptor (Fig. 5A), because pulmonary surfactant contains PG, in addition to DPPC (41). Elucidation of the roles of mLPCAT1 in the production of components of surfactant, and in other biological processes awaits gene-targeting studies.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas there has been extensive analyses of surfactant proteins A, B, C, and D (38,40), very little information is available on the mechanisms of production of surfactant lipids. Extensive analysis of surfactant composition revealed that there is 40% DPPC, and other PC, and that it contains 10% PG (41). Essentially, three distinct biosynthetic pathways are proposed to contribute to the composition of surfactant: 1) de novo biosynthesis, 2) remodeling by LPC or LPG acyltransferases, and 3) CoA-independent transacylation with 2 molecules of LPC (1, 2, 42-48).…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental studies have questioned the classical model [12,13]. Yu and Possmayer conclude that there is no evidence of lipid selectivity during the formation of surface films by adsorption.…”
Section: Pulmonary Surfactant Functionalitymentioning
confidence: 99%
“…In spite that cholesterol is present in proportions in the order of 5-10% of natural surfactants, it is systematically removed from all the clinical surfactant preparations used today, either synthetic or from animal origin. The reason is that cholesterol showed to impair surface activity in simple lipid systems tested in surface balances [47]. However, cholesterol is well recognized as a component that provides mechanical stability to cell membranes [48] and an important structural element to modulate their lateral structure, including segregation of specialized domains such as lipid rafts [49,50] contents from liposomes as well as lipid vesicle aggregation and fusion [79,80] …”
mentioning
confidence: 99%